QUALITY IN HIGHER EDUCATION THROUGH ACADEMIC AUDIT, ACADEMIC LEADERSHIP AND AUTONOMY IN INDIA - Yerande, Vitthal (PEOPLE: International Journal of Social Sciences, 2017)
The quantitative growth of higher education in India is significantly improving, but the quality of higher education has always been questioned. So, to bring quality in higher education, there is a need to change the structure of existing higher education system in India. The major roles are played in these initiatives are by the academic leaders like a Vice Chancellor of any university or a Principal of any affiliated college. The present article is focused on the role of academic leadership, continuous academic audit and accreditation process in quality enhancement and sustenance in higher education system in India. It also emphasizes the need of increasing autonomy at college level and reducing the burden of affiliation from universities. The empirical method of research has been used for the present article. The statistical data is obtained from secondary sources like books, journals, annual reports of University Grants Commission and National Assessment and Accreditation Council of India. However it is found that the higher educational institutions in India require change in academic leadership patterns as well as change in traditional teaching and learning methods and use of information and technology at large. There is an urgent need for developing a mechanism of continuous academic audit throughout all the Universities and other higher educational institutions.